PERAN CONSUMTIVE LIFESTYLE, BEAUTY VLOGGER, BRAND IMAGE, BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK KOREA (INNISFREE) DI SURABAYA - Reizano Amri Rasyid; Denis Fidita Karya (STIE Mahardhika, 2021)
This study aims to examine the effect of consumtive lifestyle, beauty vlogger, brand image and brand trust on purchasing decisions on Innisfree Korea cosmetic products. This study uses primary data derived from questionnaire respondents using Innisfree products. The sample in this study amounted to 210 respondents. Using the non-probability sampling method used in analyzing data in this study using SmartPLS 3.0. Based on the results of the analysis and hypothesis testing can be obtained the results that brand image has a negative effect on brand trust, but has a positive effect on purchasing decisions. Consumtive lifestyle has a positive effect on purchasing decisions and brand trust. Beauty vlogger has a positive effect on purchasing decisions and negatively affects brand trust. Brand trust has a positive effect on purchasing decisions.